2010
DOI: 10.2166/wst.2010.475
|View full text |Cite
|
Sign up to set email alerts
|

Combining multimedia models with integrated urban water system models for micropollutants

Abstract: Integrated urban water system (IUWS) modeling aims at assessing the quality of the surface water receiving the urban emissions through sewage treatment plants, combined sewer overflows (CSOs) and stormwater drainage systems. However, some micropollutants tend to appear in more than one environmental medium (air, water, sediment, soil, groundwater, etc.). In this work, a multimedia fate and transport model (MFTM) is "wrapped around" a dynamic IUWS model for organic micropollutants to enable integrated environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Although integrated urban water system (IUWS) modeling is usually used as a tool for evaluating the quality of the surface water receiving the municipal WWTP discharge combining sewer overflows and stormwater drainage systems, many micropollutants tend to distribute to more than one environmental compartment (air, water, sediment, soil, groundwater, etc.). Hence, a multimedia fate and transport model (MFTM) was proposed by De Keyser et al (2010) to meaningfully characterize the attenuation and distribution of micropollutants.…”
Section: Table 13mentioning
confidence: 99%
“…Although integrated urban water system (IUWS) modeling is usually used as a tool for evaluating the quality of the surface water receiving the municipal WWTP discharge combining sewer overflows and stormwater drainage systems, many micropollutants tend to distribute to more than one environmental compartment (air, water, sediment, soil, groundwater, etc.). Hence, a multimedia fate and transport model (MFTM) was proposed by De Keyser et al (2010) to meaningfully characterize the attenuation and distribution of micropollutants.…”
Section: Table 13mentioning
confidence: 99%
“…In WESTÂź, a multimedia fate and transport model (MFTM) is "wrapped around" a dynamic IUWS model for organic micropollutants to enable integrated environmental assessment ( Figure 2) (De Keyser et al, 2009b). The MFTM implemented in WESTÂź is based on the 'regional' scale of the SimpleBox model (den Hollander et al, 2003).…”
Section: Modelling Of Micro Pollutants Removal Processes In the Iuwsmentioning
confidence: 99%
“…The latter may in this example not have a vast impact, but without the MFTM shell around the IUWS model, this effect could not have been assessed at all. More details on this study can be found in De Keyser et al (2009b). …”
Section: Integration Of Iuws and Mftm Modelsmentioning
confidence: 99%
“…Large urban areas have been “waterproofed” by human activities [2], increasing the risk of higher runoff volumes [3], with increased flooding and larger pollutant loads entering water bodies [4]. Runoff in urban areas is transported in the storm sewer system, and with predictions of climate change increasing rainfall intensities and extreme events, drainage systems and treatment plants are at high risk of becoming outdated [5]. Combined sewer overflows (CSOs) are a well-known consequence of such increased surface water flows, leading to the spread of pollution over urbanised areas [6].…”
Section: Introductionmentioning
confidence: 99%